16S rRNA PCR-DGGE based bacterial community structure in activated sludge systems / Ang Pey Pey - Ang, Pey Pey (2012)
We studied bacterial community structure in three different sewage treatment plants (STPs), namely STP 1, 2 and 3, in Klang Valley. STP 1, 2 and 3 were located in residential, commercial and light-industrial areas, respectively. Cu and Pb pollution detected in STP 3 was shown to affect its sludge production and biomass. Investigation by 16S rRNA PCR-DGGE demonstrated that bacterial community structures in the three STPs were different; and heavy metal resistant bacteria were predominant at STP 3. In order to determine the effects of heavy metal pollution on bacterial community structures, we used the canonical correspondence analysis, and showed that there were two distinct groups of bacteria. The ecological distance of one group reflected the effects of both Cu and Pb pollution whereas another group mirrored the sludge volume. In this study, we showed that heavy metal pollution affected the bacterial community structure in the aeration tank. We also showed by cluster analysis of the DGGE banding patterns that the bacterial community in each STP was relatively stable. Although the stable bacterial community structure suggested acclimatization, the bacterial community in the impacted STP was not conductive for floc development, and therefore affected its efficiency.